Electroosmosis-Driven Hydrogel Actuators Using Hydrophobic/Hydrophilic Layer-By-Layer Assembly-Induced Crack Electrodes - Ko, Jongkuk; Kim, Dongjin; Song, Yongkwon; Lee, Seokmin; Kwon, Minseong; Han, Seungyong; Kang, Daeshik; Kim, Yongju; Huh, June; Koh, Je Sung; Cho, Jinhan (ACS Nano, 2020)
Development of soft actuators with higher performance and more versatile controllability has been strongly required for further innovative advancement of various soft applications. Among various soft actuators, electrochemical actuators have attracted much attention due to their lightweight, simple device configuration, and facile low-voltage control. However, the reported performances have not been satisfactory because their working mechanism depends on the limited electrode expansion by conventional electrochemical reactions. Herein, we report an electroosmosis-driven hydrogel actuator with a fully soft monolithic structure-based whole-body actuation mechanism using an amphiphilic interaction-induced layer-by-layer assembly. For this study, cracked electrodes with interconnected metal nanoparticles are prepared on hydrogels through layer-by-layer assembly and shape transformation of metal nanoparticles at hydrophobic/hydrophilic solvent interfaces. Electroosmotic pumping by cracked electrodes instantaneously induces hydrogel swelling through reversible and substantial hydraulic flow. The resultant actuator exhibits actuation strain of higher than 20% and energy density of 1.06 × 105 J m-3, allowing various geometries (e.g., curved-planar and square-pillared structures) and motions (e.g., slow-relaxation, spring-out, and two degree of freedom bending). In particular, the energy density of our actuators shows about 10-fold improvement than those of skeletal muscle, electrochemical actuators, and various stimuli-responsive hydrogel actuators reported to date.
Keywords: Device configurations; Electrochemical actuators; Electrochemical reactions; Electroosmotic pumping; Hydrophobic/hydrophilic; Layer-by-layer assemblies; Monolithic structures; Two-degree of freedom; crack electrode; electroosmosis-driven hydrogel actuator; hydrophobic/hydrophilic layer-by-layer assembly; metal nanoparticle; swelling/deswelling